Rivaroxaban for the prevention of venous thromboembolism after hip or knee arthroplasty - Turpie, Alexander G. G.; Lassen, Michael Rud; Eriksson, Bengt I.; Gent, Michael; Berkowitz, Scott D.; Misselwitz, Frank; Bandel, Tiemo J.; Homering, Martin; Westermeier, Torsten; Kakkar, Ajay K. (Thrombosis and Haemostasis, 2011)
Four phase III studies compared oral rivaroxaban with subcutaneous enoxaparin for the prevention of venous thromboembolism (VTE) after total hip or knee arthroplasty (THA or TKA). A pooled analysis of these studies compared the effect of rivaroxaban with enoxaparin on symptomatic VTE plus all-cause mortality and bleeding events, and determined whether these effects were consistent in patient subgroups. Patients (N=12,729) aged ≥18 years and scheduled for elective THA or TKA received rivaroxaban 10 mg once daily or enoxaparin 40 mg once daily or 30 mg every 12 hours. The composite of symptomatic VTE and all-cause mortality, the prespecified primary efficacy endpoint and adjudicated bleeding events were analysed in the day 12 ± 2 active treatment pool. Subgroup analyses of these outcomes were performed over the total treatment period. In the day 12 ± 2 pool, the primary efficacy endpoint occurred in 29/6,183 patients receiving rivaroxaban (0.5%) versus 60/6,200 patients receiving enoxaparin (1.0%; p=0.001). Major bleeding occurred in 21 (0.3%) versus 13 (0.2%) patients, p=0.23; major plus non-major clinically relevant bleeding in 176 (2.8%) versus 152 (2.5%) patients, p=0.19; and any bleeding in 409 (6.6%) versus 384 (6.2%) patients, p=0.38, respectively. The reduction of symptomatic VTE plus all-cause mortality was consistent across prespecified subgroups (age, gender, body weight, creatinine clearance) in the total treatment period. Compared with enoxaparin regimens, rivaroxaban reduces the composite of symptomatic VTE and all-cause mortality after elective THA or TKA, with a small increase in bleeding, no signs of compromised liver safety and fewer serious adverse events.
Keywords: Pooled analysis; rivaroxaban; venous thromboembolism